Comparison of Th1/Th2 cytokine profiles between primary and secondary haemophagocytic lymphohistiocytosis. Issue 1 (December 2016) - Chen, Yuanyuan; Wang, Zhujun; Luo, Zebin; Zhao, Ning; Yang, Shilong; Tang, Yongmin
Abstract Background Haemophagocytic lymphohistiocytosis (HLH) is a life-threatening disorder of immune regulation, and HLH patients with mutations in genes includingPRF1, UNC13D, STX11, STXBP2, SH2D1A, XIAP, andITK were reported to be primary HLH. Due to the different treatment options, the differentiation between primary and secondary HLH is critical. Our previous studies have showed that a Th1/Th2 cytokine profile is diagnostic for HLH, yet the cytokine profiles between primary and secondary HLH have not been compared. The aim of the study was to test whether the Th1/Th2 cytokine profile could be used as a tool to differentiate between primary and secondary HLH. Methods A total of 45 hospitalized Chinese children with HLH during the period of February 2010 through September 2012 were enrolled in the study. Fifty healthy children were enrolled as controls. Primary HLH related genes were sequenced using genomic DNA samples. The Th1/Th2 cytokine levels including interferon-γ (IFN-γ), tumor necrosis factor-alpha (TNF-α), interleukin (IL)-10, IL-6, IL-4 and IL-2 were quantitatively determined by cytometric bead assay techniques. Results Primary HLH group (n  = 4) included one patient with biallelic heterozygous mutations inPRF1 gene, and three patients with hemizygous mutation inSH2D1A gene. Based on the available genetic data, the other 41 patients were classified into the secondary HLH group. When compared the cytokine levels between the two groups, IL-4 level in primary-HLH was significantly lower than that in secondary HLH (P  = 0.025), while IFN-γ level in primary HLH had a tendency of statistically lower than that in secondary HLH (P  = 0.051). Area under receiver operating characteristic (ROC) curves of IL-4 and IFN-γ, IL-10, TNF-α, IL-2, and IL-6 levels were 0.841, 0.799, 0.506, 0.494, 0.457, and 0.250, respectively. ROC curves showed that 1.7 pg/ml of IL-4 had sensitivity and specificity for differentiation between primary and secondary HLH as 70.7 and 100.0 %, while 433.9 pg/ml of IFN-γ had sensitivity and specificity as 51.2 and 100.0 %, respectively. Conclusions HLH patients with lower IL-4 and IFN-γ levels have higher possibility to be primary HLH. The cytokine profile may be used as an additional tool for the quick differential diagnosis between primary and secondary HLH.